"You have to change your whole life": A qualitative study of the dynamics of treatment adherence among adults with tuberculosis in the United Kingdom. (May 2021) - Karat, Aaron S.; Jones, Annie S.K.; Abubakar, Ibrahim; Campbell, Colin N.J.; Clarke, Amy L.; Clarke, Caroline S.; Darvell, Marcia; Hill, Adam T.; Horne, Robert; Kunst, Heinke; Mandelbaum, Mike; Marshall, Ben G.; et al.
Abstract: Maintaining adherence to treatment for tuberculosis (TB) is essential if the disease is to be eliminated. As part of formative research to develop an intervention to improve adherence, we documented the lived experiences of adults receiving anti-TB treatment (ATT) in three UK cities and examined how personal, social, and structural circumstances interacted to impact on individuals' adherence to treatment. Using a topic guide that explored social circumstances and experiences of TB care, we conducted in-depth interviews with 18 adults (six women) who were being or had been treated for TB ( patients ) and four adults (all women) who were caring for a friend, relative, or partner being treated for TB ( caregivers ). We analysed transcripts using an adapted framework method that classified factors affecting adherence as personal, social, structural, health systems, or treatment-related. Eleven of 18 patients were born outside the UK (in South, Central, and East Asia, and Eastern and Southern Africa); among the seven who were UK-born, four were Black, Asian, or Minority Ethnic and three were White British. TB and its treatment were often disruptive: in addition to debilitating symptoms and side effects of ATT, participants faced job insecurity, unstable housing, stigma, social isolation, worsening mental health, and damaged relationships. Those who had a strong support network, stable employment, a routine that could easily be adapted, a trusting relationship with their TB team, and clear understanding of the need for treatment reported finding it easier to adhere to ATT. Changes in circumstances sometimes had dramatic effects on an individual's ability to take ATT; participants described how the impact of certain acute events (e.g., the onset of side effects or fatigue, episodes of stigmatisation, loss of income) were amplified by their timing or through their interaction with other elements of the individual's life. We suggest that the dynamic and fluctuating nature of these factors necessitates comprehensive and regular review of needs and potential problems, conducted before and during ATT; this, coupled with supportive measures that consider (and seek to mitigate) the influence of social and structural factors, may help improve adherence.